2019
DOI: 10.1155/2019/8783496
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Markers for Characterizing Sasang Constitution Type through GC-MS and 1H NMR-Based Metabolomics Study

Abstract: Sasang constitutional medicine classifies human beings into four types based on their physical and psychological characteristics. Despite its potential value in achieving personalized medicine, the diagnosis of sasang constitution (SC) type is complex and subjective. In this study, gas chromatography–mass spectrometry and 1H nuclear magnetic resonance–based metabolic analyses were conducted to find maker metabolites in serum and urine according to different SC types. Although some samples were overlapped on or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…One major advantage of the drug-centric approach is that the SC types cannot be falsely labeled. In the previous studies [8][9][10][11][12], the SC types were classified by the SCM doctors, after considering the patient's morphological and psychological traits. However, its diagnostic procedure can be biased by the doctor's subjective clinical experience, which means that the relative importance of traits contributing to SC-type diagnosis can vary from doctor to doctor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One major advantage of the drug-centric approach is that the SC types cannot be falsely labeled. In the previous studies [8][9][10][11][12], the SC types were classified by the SCM doctors, after considering the patient's morphological and psychological traits. However, its diagnostic procedure can be biased by the doctor's subjective clinical experience, which means that the relative importance of traits contributing to SC-type diagnosis can vary from doctor to doctor.…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite step for securing scientific evidence for SCM and expanding its application in personalized medicine is to identify biomarkers of each SC type. Previous studies, employing genome-wide association study (GWAS) and metabolomics study, have revealed genetic variations and metabolite-level biomarkers in healthy people [8][9][10][11][12]. However, the diagnosis of an SC type in these studies ultimately relied on the SCM doctors or questionnaires and was thus subject to bias due to the doctor's subjective clinical experience or low sensitivity of the questionnaire [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of personalized medicine, however, it is only possible to assume the classification principle of SCM because the classification criteria for the herbs into four Sasang type groups or the meaning of each herb belonging to each Sasang type are largely unknown. Thus far, although various studies have been conducted to find the criteria and the meaning of herbal classification [ [2] , [3] , [4] ], most studies were conducted by applying the theoretical concepts of herbs used in conventional traditional medicine or by narratively reviewing the results for each Sasang type [ 3 , 5 ]. Recently, chemical property-based various machine learning approaches have been applied to investigate natural products including herbal medicines [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metabolomics has become a powerful method to research cancer metabolism (Grønningsaeter et al, 2019). Metabolomics can be used to assess the validity of therapies by identifying endogenous small-molecule metabolites systematically and analyzing the concentration changes caused by external interference (Kim et al, 2019). Owing to the characteristics of convenient collection, feces and serum are the common samples for evaluating the effect of therapies.…”
Section: Introductionmentioning
confidence: 99%